Classroom Management to Support Active Middle Level Classrooms - Bryan Lloyd McCoy (Journal of Education and Learning (EduLearn), 2012)
This article presents a discussion of connections between middle level concepts of teaching and learning and managing a classroom through creating opportunities for active and engaged learning. The article argues and concludes that classroom management is more about managing learning than managing behavior and that one effective way to manage student behavior is to create an environment where students continuously engage in active learning (Haydon, Borders, Embury, and Clarke, 2009).